Cultural Asymmetry Between Perceptions of Past and Future Personal Change - Guo, Tieyuan; Spina, Roy (Frontiers in Psychology, 2019)
Research has shown that Westerners expect less change to occur in the future than they recall having occurred in the past. The present research investigated how recalled change and anticipated change may vary across cultures. Because Chinese perceive past times as being closer to the present than do Westerners, and people believes things tend to change more over a long period of time than over a short period of time, Chinese may perceive smaller changes from the past to the present than do Westerners. Consequently, the asymmetry between recalled change and anticipated change would disappear for Chinese. Four empirical studies revealed that for British participants, recalled changes in the past for personality, values, and the person as a whole were greater than anticipated changes in the future, whereas for Chinese, recalled changes in the past were similar in magnitude as anticipated changes in the future. Studies 2b and 3 further revealed that subjective temporal distance accounted for the cross-cultural differences in the asymmetry between recalled and anticipated changes.